Effects of superficial temporal artery to middle cerebral artery (STA-MCA) anastomosis on the cerebrospinal fluid gas tensions and pH in hemodynamically compromised patients - Kuroda, Satoshi; Yamamoto, Shusuke; Hori, Emiko; Kashiwazaki, Daina; Noguchi, Kyo (Acta neurochirurgica, 2023)
Purpose This study was aimed to directly measure cerebrospinal fluid (CSF) gas tensions and pH before and after STA-MCA anastomosis for occlusive carotid artery diseases to investigate its direct effects on the ischemic brain. Methods This study included 9 patients who underwent STA-MCA anastomosis on the basis of CBF studies. About 1 mL of CSF was collected before and after bypass procedures, and CSF pH, CSF PO 2 , and CSF PCO 2 were measured with a blood gas analyzer. As the controls, the CSF was collected from 6 patients during surgery for unruptured cerebral aneurysm. CSF PO 2 and CSF PCO 2 were expressed as the ratio to PaO 2 and PaCO 2 , respectively. Results Before bypass procedure, CSF PO 2 /PaO 2 was 0.88 ± 0.16, being lower than the controls (1.10 ± 0.09; P = 0.005). CSF PCO 2 /PaCO 2 was 0.93 ± 0.13, being higher than the controls (0.84 ± 0.06; P = 0.039). Ipsilateral-to-contralateral CBF ratio had a positive correlation with CSF PO 2 /PaO 2 ( P = 0.0028) but a negative correlation with the CSF PCO 2 /PaCO 2 ( P = 0.0045). STA-MCA anastomosis increased CSF pH from 7.402 ± 0.133 to 7.504 ± 0.126 ( P = 0.0011) and CSF PO 2 /PaO 2 from 0.88 ± 0.16 to 1.05 ± 0.26 ( P = 0.018) but decreased CSF PCO 2 /PaCO 2 from 0.93 ± 0.13 to 0.70 ± 0.17 ( P = 0.0006). Conclusion The severity of cerebral ischemia before surgery is intensely reflected in the gas tensions and pH of the CSF. STA-MCA anastomosis carries dramatic effects on CSF gas tensions and pH in hemodynamically compromised patients. CSF would be a valuable surrogate biomarker to monitor the severity of cerebral ischemia.